Theoretical and experimental characterization of trivalent lanthanide (La-Eu) aquacomplexes with losartan - Santos, Anderson José dos; Serafim, Ana Carolina Cunha; Siqueira, Adriana de Paula Cardoso; Teixeira, José Augusto; de Souza, Aguinaldo R. [UNESP]; Morgon, Nelson H.; Siqueira, Adriano B. (Elsevier, 2024)
In this work, losartan compounds with trivalent ions La(III), Ce(III), Pr(III), Nd(III), Sm(III), and Eu(III) were synthesized in the solid-state. The thermal and spectroscopic study of the compounds was performed using TG-DSC, FTIR, DRX, and evolved gas analysis (EGA) by TG-DSC/FTIR. The theoretical and experimental spectroscopic data suggested the possible modes of coordination of the ligand with the metal ions by the tetrazole ring. Thermogravimetric analyses provide information on the thermal stability, water coordination, and stoichiometry of the compounds. The minimum formulae of the compounds is [Ln(Los)3(H2O)x], where Ln=La and Ce/x = 7; and Pr, Nd, Sm, Eu/x = 6. TG-DSC coupled to FTIR in an air atmosphere suggested the release of H2O, CO2, CO, MeOH, NH3, and -NCO during the thermal decomposition of losartan from lanthanides. Amorphous compounds were obtained, and their poor solubility suggests their potential use as prodrugs in the solid-state.
Keywords: Ab Initio; Antiprism geometry; Losartan; Prism Geometry; Trivalent lanthanides